Photoinduced Deaminative C(sp3)–H Bond diarylation of glycine derivatives by cerium catalysis - Wang, Shutao; Liao, Jinyi; Li, Yukang; Zhang, Yuan; Guo, Li-Na (Synthesis, 2025)
A Ce(III)-catalyzed, visible light–induced aerobic oxidative diarylation of glycine derivatives with electron-rich aromatics is described. This method enables the efficient and rapid synthesis of diarylmethane derivatives under mild conditions, using air as the oxidant and obviating the need for an external photosensitizer. It is noteworthy that this protocol can be scaled up to 5 mmol without a significant impact on the efficiency.
Keywords: Glycine derivative; Visible-light induced; Photosensitizers free; Diarylation; Cerium catalysis